Effects of isometric muscle training on shoulder pain, function and performance in bowlers: A randomized clinical trail - Sheeraz Ali; Ubaid Ullah; Riafat Mehmood; Osama Faisal; Helping Hand Rehabilitation Center Lower Dir Khyber Pakhtunkhwa Pakistan; Muhammad Khalil ur Rehman (The Rehabilitation Journal)
Background: Overuse injuries with shoulder pain are one of the most common complaints among cricket bowlers, leading to reduced performance, and ultimately affecting an athlete's career and overall well-being. Isometric muscle training (IMT) is gaining attention as an effective intervention for musculoskeletal pain and functional performance.